2014
DOI: 10.1371/journal.pone.0098943
|View full text |Cite
|
Sign up to set email alerts
|

Glabridin Mediate Caspases Activation and Induces Apoptosis through JNK1/2 and p38 MAPK Pathway in Human Promyelocytic Leukemia Cells

Abstract: BackgroundGlabridin, a prenylated isoflavonoid of G. glabra L. roots, has been associated with a wide range of biological properties such as regulation of energy metabolism, estrogenic, neuroprotective, anti-osteoporotic, and skin-whitening in previous studies. However, the effect of glabridin on tumor cells metastasis has not been clearly clarified. Here, the molecular mechanism by which glabridin anticancer effects in human promyelocytic leukemia cells was investigated.Methodology and Principal FindingsThe r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 41 publications
3
32
1
Order By: Relevance
“…These findings are consistent with those of a previous report [23]. Recent studies have suggested a key role for p38 MAPK and JNK in mediating pathways leading to apoptosis and growth-inhibitory signals [37,38]. Additionally, p38 MAPK and JNK trigger caspase-3 activation and are also necessary for the phosphorylation of apoptosis-related proteins, including Bax and Bcl-2, in cancer cells [23,39].…”
Section: Melatonin Enhances the Effectiveness Of Cisplatin By Suppressupporting
confidence: 93%
“…These findings are consistent with those of a previous report [23]. Recent studies have suggested a key role for p38 MAPK and JNK in mediating pathways leading to apoptosis and growth-inhibitory signals [37,38]. Additionally, p38 MAPK and JNK trigger caspase-3 activation and are also necessary for the phosphorylation of apoptosis-related proteins, including Bax and Bcl-2, in cancer cells [23,39].…”
Section: Melatonin Enhances the Effectiveness Of Cisplatin By Suppressupporting
confidence: 93%
“…These pathways have been known to be involved in hematopoiesis and lymphomagenesis (4550). These data indicate that postirradiation hematopoietic protection by GT3 might be regulated through the ERK/P38-MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…For flow cytometric analysis of sub‐G1 cell counting with fragmented DNA, HL‐60 cells (2 × 10 6 /mL) were treated with vehicle or CAC (0, 2.5, 5, or 10 μM) for 24 h and then cells were collected and fixed by 70% cold ethanol for 2 h at −20°C and then washed with PBS as previously described . Next, Cell pellets were incubated with 10 mg mL −1 RNase at 37°C for 30 min before adding propidium iodide (PI) buffer [4 μg mL −1 PI, 0.5 mg mL −1 RNase A, and 1% Triton X‐100 in phosphate‐buffered saline (PBS)] for 30 min at 37°C in the dark followed by filtration through a 40‐μm nylon filter (Falcon, San Jose, CA).…”
Section: Methodsmentioning
confidence: 99%